2016
DOI: 10.4236/aid.2016.61003
|View full text |Cite
|
Sign up to set email alerts
|

Higher Type 1 Interferon Levels in Plasma of Asymptomatic HIV-2 than in HIV-1 Individuals

Abstract: A number of cytokines are secreted during HIV infection that enhances both innate and adaptive immune responses. Interferon-α/β/γ, IL-12, IL-15 and IL-18 have been found to contribute to the development, maturation, differentiation and function of NK and other immune cells. The levels of IFN-α/β/γ, IL-12, IL-15 and IL-18 were compared in the plasma of 90 HIV-1 infected and 90 HIV-2 infected subjects by ELISA or Cytometric Beads Array assays. The HIV-infected subjects were stratified according to CD4 + T cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…Another reason for increased levels of IFN-α could be low CD4 count which may be due to the fact that infection of HIV as well as P.falciparumhas been known to induce depletion of CD4 T-cells and to reduce CD8 T-cells causing downmodulation, reduction in T-cell sub-population and defective cell mediated immunity against any microbial infection (Kirinyet, 2019). This study however, contradicts the findings of Nuvor et al (2016) which suggests that high levels of IFN-α may be supporting the persistently high CD4+ T cell numbers in HIV infection from an early stage of infection.…”
Section: Relationship Between Parasitaemia and Cd4 Countcontrasting
confidence: 51%
See 1 more Smart Citation
“…Another reason for increased levels of IFN-α could be low CD4 count which may be due to the fact that infection of HIV as well as P.falciparumhas been known to induce depletion of CD4 T-cells and to reduce CD8 T-cells causing downmodulation, reduction in T-cell sub-population and defective cell mediated immunity against any microbial infection (Kirinyet, 2019). This study however, contradicts the findings of Nuvor et al (2016) which suggests that high levels of IFN-α may be supporting the persistently high CD4+ T cell numbers in HIV infection from an early stage of infection.…”
Section: Relationship Between Parasitaemia and Cd4 Countcontrasting
confidence: 51%
“…Interferons (IFNs) are a multigene family of inducible cytokines produced by the host immune system which are among the key molecules in the early defense against infections and are in many cases the first line of resistance to many viral and protozoan infections (McNab et al, 2015;Silva-Barrios and Stager, 2017). IFN-Is, particularly IFN-α, appear to be protective in human infections of P. falciparum (Subramaniam et al, 2015) and HIV infections (Nuvor et al, 2016). Studies have also shown associations between high levels of IFN-α produced early during an infection with protection (Subramaniam et al, 2015).On the other hand, excess production of IFN-α have been shown to cause immunopathology leading to immunosuppression (Davidson et al, 2014;Lukhele et al, 2019).…”
Section: Introductionmentioning
confidence: 99%